A Theory of Harmony : With A New Introduction by Paul Wilkinson - Levy, Ernst (State University of New York Press, 2024)
Ernst Levy was a visionary Swiss pianist, composer, and teacher who developed an approach to music theory that has come to be known as "negative harmony." Levy's theories have had a wide influence, from young British performer/composer Jacob Collier to jazz musicians like Steve Coleman. His posthumous text, A Theory of Harmony, summarizes his innovative ideas. A Theory of Harmony is a highly original explanation of the harmonic language of the modern era, illuminating the approaches of diverse styles of music. By breaking through age-old conceptions, Levy was able to reorient the way we experience musical harmony. British composer/music pedagogue Paul Wilkinson has written a new introduction that offers multiple points of entry to Levy's work to make this text more accessible for a new generation of students, performers, and theorists. He relates Levy's work to innovations in improvisation, jazz, twentieth-century classical music, and the theoretical writings of a wide range of musical mavericks, including Harry Partch, Hugo Riemann, and David Lewin. Wilkinson shows how A Theory of Harmony continues to inspire original musical expression across multiple musical genres.
Frontmatter -- Contents -- New Introduction -- Editor's Preface to the First Edition -- Pitch Designations -- Foreword to the First Edition -- 1. Tone Structure -- 2. Polarity -- 3. The Triad -- 4. Consonance-Dissonance -- 5. The Natural Seventh -- 6. Temperament -- 7. Tonal Functions of Intervals -- 8. Tonal Functions of Triads -- 9. Tonal Functions of Nontriadic and Compound Chords -- Summary -- Appendices
Machine-generated record
JSTOR
Keywords: Harmony; Harmonie; Theory; Composition; Instruction & Study; MUSIC; Phenomenology; Movements; PHILOSOPHY; Electronic books